Radical respect [book club bag]: how to work together better - Scott, Kim (Kim Malone) (St. Martin's Griffin, 2024)
"We CAN create cultures where everyone does the best work of their lives and enjoys working together. Radical Respect offers a simple framework that helps us identify what gets in the way of that -and practical, tactical tips for how to get back on track. Candid stories from Scott's career make it a memorable read. Previously published as Just Work and now substantially revised and updated, Radical Respect starts from a simple point of departure: organizations that optimize for collaboration and honor everyone's individuality are more successful, joyful places to work. What moves us away from Radical Respect? Scott offers a "toxonomy" that breaks down a problem that often feels monolithic into its component parts. Once we break a problem down, we can more easily identify solutions."--